2011
DOI: 10.1007/s10522-011-9370-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of oxidative stress biomarkers in renal tissues of d-galactose induced, naturally aged and young rats

Abstract: Ageing of kidneys is a clinical health issue of the society. Age-related renal insufficiency has important implications due to impaired redox homeostasis. We examined protein, DNA and lipid oxidation biomarkers as well as protein-bound sialic acid (SA) in the kidney tissues of D-galactose induced ageing rats, naturally aged rats and their corresponding young control group. Intraperitoneal injection of D-galactose (60 mg/kg/day) for 6 weeks to young male Sprague-Dawley rats (20-week-old) was used to establish m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 50 publications
(48 reference statements)
3
33
1
2
Order By: Relevance
“…liver and blood cells (Lei et al, 2008;Xie and Ling, 2008;Aydin et al, 2012;Hsia et al, 2012;Wu et al, 2012) more recently, we found phenotypes of Polycystic Ovary Syndrome (PCOS) in this model (Park and Choi, 2012). These induced phenotypes may be the result of excessive formation of Reactive Oxygen Species (ROS) and D-gal-induced accumulation of AGEs (Song et al, 1999).…”
Section: Ajimentioning
confidence: 79%
“…liver and blood cells (Lei et al, 2008;Xie and Ling, 2008;Aydin et al, 2012;Hsia et al, 2012;Wu et al, 2012) more recently, we found phenotypes of Polycystic Ovary Syndrome (PCOS) in this model (Park and Choi, 2012). These induced phenotypes may be the result of excessive formation of Reactive Oxygen Species (ROS) and D-gal-induced accumulation of AGEs (Song et al, 1999).…”
Section: Ajimentioning
confidence: 79%
“…Recently, studies focused on the roles of galactose in cellular senescence have shown that the mechanisms underlying d -gal -induced aging likely involve glucose and 1ipid metabolic disorders, increased oxidative damage, the accumulation of advanced glycation end products, impaired elimination of abnormal substances, accelerated cell apoptosis, and enhanced insulin resistance 22,24. The effects produced by d -gal differ with dosage (varying between 50 and 1,250 mg/kg/d), age group (varying between 6 weeks and 6 months), and time interval (varying between 6 and 10 weeks) 12. According to the literature,14,15 we induced aging in 12-weeks-old rats using two different d -gal doses (125 mg/kg/d and 500 mg/kg/d).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the aforementioned pathologic states, tissue factors such as protein, deoxyribonucleic acid, and lipid oxidation products are associated with renal aging 3,4…”
Section: Introductionmentioning
confidence: 99%